Sequence ability in parkinsonians, patients with frontal lobe lesions and patients who have undergone unilateral temporal lobectomies. - Canavan, A; Passingham, R; Marsden, C; Quinn, N; Wyke, M; Polkey, C (1989)
Patients in the early stages of Parkinson's disease were compared with patients who had sustained damage specific to either the frontal or temporal lobes and normal controls on a number of sequencing tests. These tests involved the reproduction of sequences of hand gestures, sequences tapped out on blocks, and sequences of digits. Only the groups with frontal lobe lesions or right temporal lobectomies were impaired on any of these tasks, though no group was impaired on all of the sequencing tasks.